Is automated platelet counting still a problem in thrombocytopenic blood? - Oliveira, Raimundo Antônio Gomes; Takadachi, Maria Mariko; Nonoyama, Kimiyo; Barretto, Orlando César de Oliveira (São Paulo Medical Journal, 2003)
CONTEXT: Reliable platelet counting is crucial for indicating prophylactic platelet transfusion in thrombocytopenic patients. OBJECTIVE: To evaluate the precision and accuracy of platelet counting for thrombocytopenic patients, using four different automated counters in comparison with the Brecher & Cronkite reference method recommended by the International Committee for Standardization in Hematology (ICSH). TYPE OF STUDY: Automated platelet counting assessment in thrombocytopenic patients. SETTING: Hematology Laboratory, Hospital do Servidor Público Estadual de São Paulo, and the Hematology Division of Instituto Adolfo Lutz, São Paulo, SP, Brazil. MAIN MEASUREMENTS: Brecher & Cronkite reference method and four different automated platelet counters. PARTICIPANTS: 43 thrombocytopenic patients with platelet counts of less than 30,000/µl RESULTS: The ADVIA-120 (Bayer), Coulter STKS, H1 System (Technicom-Bayer) and Coulter T-890 automatic instruments presented great precision and accuracy in relation to laboratory thrombocytopenic samples obtained by diluting blood from normal donors. However, when thrombocytopenic patients were investigated, all the counters except ADVIA (which is based on volume and refraction index) showed low accuracy when compared to the Brecher & Cronkite reference method (ICSH). The ADVIA counter showed high correlation (r = 0.947). However, all counters showed flags in thrombocytopenic samples. CONCLUSION: The Brecher & Cronkite reference method should always be indicated in thrombocytopenic patients for platelet counts below 30,000 plt /µl obtained in one dimensional counters.